THE ROLE OF E-BUPOT UNIFICATION APPLICATION IN MODERATING SERVICE QUALITY, TAX MORALITY, AND TAX PENALTIES ON TAXPAYER REPORTING COMPLIANCE - Fahmi; Jamaluddin; Furqan, Andi Chairil; Amir, Andi Mattulada; Zahra, Femilia; Din, Muhammad; Rahmawaty, Santi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This study analyzes the effects of service quality, tax morale, and tax penalties on tax reporting compliance, with the e-Bupot Unification application as a moderating variable. Focusing on Regional Government Organizations (OPDs) under the Palu Tax Office (KPP Pratama Palu) in Central Sulawesi, it addresses low tax reporting (SPT Masa) despite 100% tax payment rates. Data were collected from OPD treasurers through questionnaires and analyzed using Partial Least Squares (PLS) with WarpPLS software. Results show that service quality, tax morale, and tax penalties  improve tax reporting compliance. However, the e-Bupot Unification application fails to strengthen the relationship between tax morale and sanctions with compliance, and negatively moderates the link between service quality and compliance due to system complexity, limited user understanding, and resistance to technology. This study contributes to taxation literature and suggests improving service quality, promoting tax morale through education, and consistently enforcing sanctions. To optimize e-Bupot Unification, the government should simplify the system and expand user training efforts.